How market-based water allocation can improve water use efficiency in the Aral Sea basin - Bekchanov, Maksud; Bhaduri, Anik; Ringler, Claudia (2013)
Increasing water demand due to population growth and economic development under the mounted investment costs for developing new water sources calls for efficient, equitable and sustainable management of water resources in many developing countries. This is more essential in the Aral Sea basin where the tremendous development in irrigation since the 1960s combined with unbalanced water resources management led to the destruction of the ecosystems in the delta zone and the gradual desiccation of the Aral Sea, once the fourth biggest lake of the world with a surface area of 68,000 km2 and total water volume of 1,100 km3. Disintegration of the Central Asian states after the collapse of the Soviet Union also increased the tensions among up- and downstream users over sharing water resources. Insufficient investments in irrigation infrastructure, lack of economic incentives to adopt water-wise approaches, and inefficient water governance and institutions have been the main reasons of decreased water use efficiency in the post-Soviet period. Market-based water allocation is tested to deal with aggravating water conflicts in the Aral Sea basin. Aggregated integrated hydro-economic model is constructed to analyze the water market mechanism as an alternative option to the traditional administrative water allocation. Water users are allowed to trading their water use rights and increasing their benefits under this decentralized water management system. The analyses show the availability of additional gains amounted to US$ 373 to 476 million under inter-catchment water trading depending on the level of water availability. Similarly, additional gains of US$ 259 to 339 million are estimated under intra-catchment water trading. Furthermore, increased trend of additional gains from water trading along with decreased water availability are found. However, transaction costs of introducing tradable water rights are essential to judge the effectiveness of water market reforms and initiate appropriate institutional changes. According to our estimations, transaction costs of more than 5 C/m3 of traded water use rights eliminate the potential benefits of the water trading option. Friendly relationships among the riparian countries and infrastructural improvements are suggested as a means of developing low cost enforcement of water trading contracts.